THE EFFICIENCY OF IMMUNE MODULATOR BIVEL IN THE PREVENTION OF PULMONARY TUBERCULOSIS IN EXPOSED CHILDREN FROM THE MULTIDRUG-RESISTANT TUBERCULOSIS SITES - Olha SAKHELASHVILI-BIL; Iryna PLATONOVA (Academy of Sciences of Moldova, 2024)
120 exposed children/adolescents (75 children and 45 adolescents) from the multi-drug resistant tuberculosis sites underwent the complex clinical radiological and immunological examination.Insignificant functional disorders of cellular response (immunoregulatory processes) caused by the prevalence of suppressor and cytotoxic reactions by 1.3 times and by the prevalence of pro-inflammatory cytokines in the regulatory system (2.0 times above the norm, TNF-α/IL 10.0. р<0.01) were revealed in the infected children/adolescents from the multi-drug resistant tuberculosis sites, while their СD3+. СD3+СD4+. СD3+СD8+ were within norm. The evident disorders of the regulatory system and cell immune system were eliminated after the completion of the autumn-spring BI-V course. The non-specific immune regulator BI-V is efficient for the prevention of multi-drug resistant tuberculosis for the exposed children/adolescents from the multi-drug tuberculosis sites. Consequently, the latent TB infection grew into the active form by 2.8 times less often in the children that took BI-V as compared to the infected children who did not take the drug.